Changes in the disparity vergence main sequence after treatment of symptomatic convergence insufficiency in children - Mitchell Scheiman; Chang Yaramothu; Tara L. Alvarez (Journal of Eye Movement Research)
This study investigates the underlying physiological mechanisms that may lead to improved outcomes for symptomatic convergence insufficiency (CI) patients after 12 weeks of office-based vergence/accommodation therapy (OBVAT) by evaluating the change in the main sequence of vergence and saccadic eye movements. In this prospective trial, 12 participants with symptomatic CI were recruited and treated with 12 weeks of OBVAT. Outcome measures included the objective assessment of the following: peak velocity, time to peak velocity, latency, response amplitude, and clinical changes in the near point of convergence (NPC), positive fusional vergence (PFV) and symptoms via the Convergence Insufficiency Symptom Survey (CISS). Ten of the twelve participants (83%) were categorized as “successful” and two were “improved” based on pre-determined published criteria (CISS, NPC, PFV). There were statistically significant changes in peak velocity, time to peak velocity, and response amplitude for both 4° and 6° symmetrical convergence and divergence eye movements. There was a significant change in the main sequence ratio for convergence post-OBVAT compared to baseline measurements (P=0.007) but not for divergence or saccadic responses. Phasic/step vergence movements adjust the underlying neural control of convergence and are critical within a vision therapy program for CI patients.